ANALYSIS OF TECHNOLOGICAL COMPETITIVENESS THROUGH MANAGERIAL RELATIONSHIPS AND MARKETING INNOVATION WITH CUSTOMER VALUE INTERVENTION IN THE TELECOMMUNICATIONS INDUSTRY COMPETITION IN INDONESIA WITH STARLINK - Azizi Hakim Komara (RADJA PUBLIKA, 2026)
The increase in internet penetration in Indonesia has led to increasingly fierce competition in the internet service provider industry, especially with the arrival of satellite-based services such as Starlink, which offers high-speed technology and wide coverage. This situation requires local internet service providers to improve their technological competitiveness through appropriate strategies. This study aims to analyze the influence of managerial relationship capabilities and marketing innovation on technological competitiveness with the mediating role of customer value. The study uses a quantitative approach with a survey method of 150 respondents who are internet service users. Data were collected through an online questionnaire and analyzed using SmartPLS-based Structural Equation Modeling (SEM). The results of the study indicate that managerial relationships and marketing innovation do not directly affect technological competitiveness. However, both variables have an indirect effect through customer value as a mediating variable. Customer value is also proven to have a positive and significant effect on technological competitiveness. These findings confirm that the creation of customer value is a key factor in enhancing technology-based competitive advantage in the telecommunications industry. Therefore, companies need to focus their managerial strategies and marketing innovation on efforts to increase perceived customer value in order to maintain competitiveness amid increasingly dynamic technological competition.